A dimensão pedagógica da ação do nutricionista: um estudo dos projetos de formação no Brasil, Argentina e Portugal - Pedroso, Maisa Beltrame (Universidade do Vale do Rio dos Sinos, 2012)
Several countries have conducted reforms in undergraduate teaching aiming to integrate its functions to the needs of society, having as background the production of knowledge to prepare the human capital to meet the inclusion in the circuit of globalization. This is the case of courses in the area of health, and under the perspective of this doctoral study-- the Nutrition course. Without minimizing the importance of technical skills in the training of students, these demands require new curricular settings and different educational practices. Understanding the nutritionist´s professional exercise, as an eminently pedagogical action, refers to rethinking academic practices experienced in his/her training and the role of trainers in this context. Although one can consider this phenomenon as a global process, experiments in this study were taken from Nutrition Training Courses in Portugal, Argentina and Brazil. At first we selected the course of Nutrition of the School of Science of Nutrition and Food- (FCNAUP) at the University of Porto; in Argentina, the Escuela de Nutrición da Facultad de Medicina at the University of Buenos Aires, and in Brasil, the Course of Nutrition of the Federal University of São Paulo- Baixada Santista campus. The Brazilian experience was chosen for characterizing itself as a unique experience in its curricular and methodological approach. The other choices are the result of sandwich doctoral studies in the respective countries. The research took a qualitative approach, with inspiration from ethnographic principles. Seventeen interviews were conducted with the faculty, undergraduates and graduates, trying to understand whether and how the pedagogical dimension is present in the nutritionist training and whether it influences the knowledge of this professional. Legal documents that involve the formation of the three courses were also examined. In the course of the research it was possible to observe that the Pedagogical Political Projects, while manifestation of the organization of the courses sought to be the starting point for curriculum development and innovation, toward the integration of knowledge and practices that value the collective learning. The pedagogical dimension of the professional nutritionist appears differently in the legislation and in the proposed curriculum of the three courses, in the respective countries. While this aspect is emphasized in the Brazilian Curricular Guidelines, in other countries it seems to be a value for the academic communities, but expressed with more cloudiness in educational legislation. Probably this condition is favored by the adequacy of education to health policies, after the creation of the Unified Health System (SUS) in Brazil. The creation of participatory Pedagogical Project focuses on the knowledge of the faculty and their commitment to its principles, as it was revealed in the three realities studied. The relation between theory and practice appears to be essential for the formation in the sense of promoting the vision of reality that underlies the knowledge and commitment of the students. In this sense it seems fundamental the establishment of relationships between the university and health services that must act together for the training of future professionals. The educational process developed in a collective way in which all actors involved such as the faculty, undergraduates and community learn jointly, favors the development of autonomy, providing conditions to transform the individual into a subject of greater solidarity.The research, which aimed to investigate the contemporary settings of the professional nutritionist training, sought to contribute to the quality of training and expand the scenarios and possibilities for an educational practice consistent with the demands of a fairer society and greater welfare. It bet on the value of the pedagogical dimension of the action of those who work in the field of health that also includes the design of knowledge-sharing and solidarity, creating conditions for the awareness that the main activity of the professional nutritionist is to promote the humanization of individuals
Keywords: Práticas educativas; Cursos de nutrição; Projeto político pedagógico; Educational practices; Nutrition courses; Political pedagogical project; ACCNPQ::Ciências Humanas::Educação